Effect of the Optimize Heart Failure Care Program on clinical and patient outcomes – The pilot implementation in Vietnam. (March 2019) - Do, Thi Nam Phuong; Do, Quang Huan; Cowie, Martin R.; Ha, Ngoc Ban; Do, Van Dung; Do, Thi Hao; Nguyen, Thi Thuy Hang; Tran, Thuy Loan; Nguyen, Thi Ngoc Oanh; Nguyen, Thi My Hanh; Chau, Thi To Quyen; Nguyen, Thi Tuyen Tien; et al.
Abstract: Background: The Ho-Chi-Minh-city Heart Institute in Vietnam took part in the Optimize Heart Failure (OHF) Care Program, designed to improve outcomes following heart failure (HF) hospitalization by increasing patient awareness and optimizing HF treatment. Methods: HF patients hospitalized with left ventricular ejection-fraction (LVEF) <50% were included. Patients received guideline-recommended HF treatment and education. Clinical signs, treatments and outcomes were assessed at admission, discharge, 2 and 6 months (M2, M6). Patients' knowledge and practice were assessed at M6 by telephone survey. Results: 257 patients were included. Between admission and M2 and M6, heart rate decreased significantly, and clinical symptoms improved significantly. LVEF increased significantly from admission to M6. 85% to 99% of patients received education. At M6, 45% to 78% of patients acquired knowledge and adhered to practice regarding diet, exercise, weight control, and detection of worsening symptoms. High use of renin-angiotensin-aldosterone-system inhibitors (91%), mineralocorticoid-receptor-antagonists (77%) and diuretics (85%) was noted at discharge. Beta-blocker and ivabradine use was less frequent at discharge but increased significantly at M6 (from 33% to 51% and from 9% to 20%, respectively, p  < 0.001). There were no in-hospital deaths. Readmission rates at 30 and 60 days after discharge were 8.3% and 12.5%, respectively. Mortality rates at 30 days, 60 days and 6 months were 1.2%, 2.5% and 6.4%, respectively. Conclusions: The OHF Care Program could be implemented in Vietnam without difficulty and was associated with high usage of guideline-recommended drug therapy. Although education was delivered, patient knowledge and practice could be further improved at M6 after discharge.